Varanoid lizards of the world - Pianka, Eric R.; King, Dennis, 1942-; King, Ruth Allen (Indiana University Press, 2004)
"Varanoid Lizards of the World is a comprehensive account of virtually everything important that is known about monitor lizards and their allies, beginning with detailed species accounts and proceeding to various modern comparative analyses. Where possible, people who have had detailed field experience with particular species have assembled the corresponding species accounts."--Jacket.